Structural Design of 5 mol.% Yttria Partially Stabilized Zirconia (5Y-PSZ) by Addition of Manganese Oxide and Direct Firing - Alejandro Natoli; Aleksey Yaremchenko; Jorge R. Frade (Ceramics, 2020)
In this study, 5Y-PSZ-based ceramics with 15 mol.% of manganese oxide were obtained from PSZ + MnO2 powders mixtures by pressing and direct firing. The resulting materials show a stable cubic fluorite structure with only minor traces of segregated manganese oxides and relative density from 90% to 98%. The linear thermal expansion coefficient is in the order of 10−5 K−1 at 500 K and increases gradually with temperature, due to the onset of a contribution of chemical expansion, reaching about 13 × 10−6 K−1 at 1100 K. These results are suitable for prospective applicability as buffer layers to minimize degradation and delamination of electrolyte/oxygen electrode interfaces in solid electrolyte cells. The electrical conductivity remains close to 1 S/m at 973 K and close to 7 S/m at 1273 K, suggesting mixed conductivity with a prospective contribution to electrode processes occurring at electrode/electrolyte interfaces. Guidelines for further improvement were also established by a detailed analysis of the impact of heating/cooling rate, firing temperature, and time on those properties, based on Taguchi planning.